DCT4—A New Member of the Dicarboxylate Transporter Family in C4 Grasses. (2nd February 2021) - Weissmann, Sarit; Huang, Pu; Wiechert, Madeline A; Furuyama, Koki; Brutnell, Thomas P; Taniguchi, Mitsutaka; Schnable, James C; Mockler, Todd C
Abstract: Malate transport shuttles atmospheric carbon into the Calvin–Benson cycle during NADP-ME C4 photosynthesis. Previous characterizations of several plant dicarboxylate transporters (DCT) showed that they efficiently exchange malate across membranes. Here, we identify and characterize a previously unknown member of the DCT family, DCT4, in Sorghum bicolor . We show that SbDCT4 exchanges malate across membranes and its expression pattern is consistent with a role in malate transport during C4 photosynthesis. SbDCT4 is not syntenic to the characterized photosynthetic gene ZmDCT2, and an ortholog is not detectable in the maize reference genome. We found that the expression patterns of DCT family genes in the leaves of Zea mays, and S. bicolor varied by cell type. Our results suggest that subfunctionalization, of members of the DCT family, for the transport of malate into the bundle sheath plastids, occurred during the process of independent recurrent evolution of C4 photosynthesis in grasses of the PACMAD clade. We also show that this subfunctionalization is lineage independent. Our results challenge the dogma that key C4 genes must be orthologues of one another among C4 species, and shed new light on the evolution of C4 photosynthesis.